2016
DOI: 10.1371/journal.pone.0159865
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Analysis of Four New Alleles at the W1 Locus Associated with Flower Color in Soybean

Abstract: In soybean, flavonoid 3′5′-hydroxylase (F3′5′H) and dihydroflavonol-4-reductase (DFR) play a crucial role in the production of anthocyanin pigments. Loss-of-function of the W1 locus, which encodes the former, or W3 and W4, which encode the latter, always produces white flowers. In this study, we searched for new genetic components responsible for the production of white flowers in soybean and isolated four white-flowered mutant lines, i.e., two Glycine soja accessions (CW12700 and CW13381) and two EMS-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Anthocyanins and carotenoids are considered to be the main pigments involved in coloration of raspberries (de Ancos et al, 1999; Carvalho et al, 2013b). Anthocyanins are water soluble polyphenolic pigments responsible for the colors of many flowers (Chung et al, 2010; Luo et al, 2015; Sundaramoorthy et al, 2016), fruits (Saito et al, 1999; Debes et al, 2011; Liu et al, 2013; Ben-Simhon et al, 2015), and other plant tissues (Gould et al, 2000; Kim et al, 2004; Zhou et al, 2010). Their biochemical role in plants is not fully understood, however, they have been considered to protect tissues from biotic and abiotic stresses, delay in senescence, assist in photosynthetic machinery, delay over-ripening and increase shelf-life of fruits and act as scavengers of reactive oxygen intermediates (Zhang et al, 2013, 2016; Landi et al, 2015; Yousuf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Anthocyanins and carotenoids are considered to be the main pigments involved in coloration of raspberries (de Ancos et al, 1999; Carvalho et al, 2013b). Anthocyanins are water soluble polyphenolic pigments responsible for the colors of many flowers (Chung et al, 2010; Luo et al, 2015; Sundaramoorthy et al, 2016), fruits (Saito et al, 1999; Debes et al, 2011; Liu et al, 2013; Ben-Simhon et al, 2015), and other plant tissues (Gould et al, 2000; Kim et al, 2004; Zhou et al, 2010). Their biochemical role in plants is not fully understood, however, they have been considered to protect tissues from biotic and abiotic stresses, delay in senescence, assist in photosynthetic machinery, delay over-ripening and increase shelf-life of fruits and act as scavengers of reactive oxygen intermediates (Zhang et al, 2013, 2016; Landi et al, 2015; Yousuf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our phylogenetic analysis of soybean DFR2 genes indicated that the reported kw4 DFR2 sequence itself was questionable because its structure appeared to be either an artificial chimera or natural hybrid between G. soja and G. max. Concern about the significance of the 367-bp deletion in the third intron of the sequence was also expressed by Sundaramoorthy et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…When compared with those of Hwangkeum and Clark bearing purple flowers, >20 SNPs and insertion-deletion events were observed in the five intron regions. However, only one synonymous SNP was identified in the exon region, indicating that the same amino acid sequence was encoded by DFR2 in both YWS415 and W4 soybean accessions in the absence of the transposon insertion (Xu et al, 2010;Yan et al, 2014;Sundaramoorthy et al, 2016).…”
Section: Nucleotide Sequence and Genetic Analysis Of The Locus Conditmentioning
confidence: 97%
See 2 more Smart Citations